1996
DOI: 10.1007/bf02110109
|View full text |Cite
|
Sign up to set email alerts
|

Size and selectivity of gap junction channels formed from different connexins

Abstract: Gap junction channels have long been viewed as static structures containing a large-diameter, aqueous pore. This pore has a high permeability to hydrophilic molecules of approximately 900 daltons in molecular weight and a weak ionic selectivity. The evidence leading to these conclusions is reviewed in the context of more recent observations primarily coming from unitary channel recordings from transfected connexin channels expressed in communication-deficient cell lines. What is emerging is a more diverse view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
171
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(180 citation statements)
references
References 42 publications
8
171
0
1
Order By: Relevance
“…This phenomenon was not related to a greater or lesser potent inhibitory effect on the proliferation of the transfected tumor cells. Recent observations criticizing the conventional gap junction model based solely on size restriction, [34][35][36] are consistent with our hypothesis that gap junction might be differentially permeable to a variety of nucleotides. Purine nucleoside analogues may effectively cross the gap junctions once they have been converted to their monophosphate form (by the viral TK) and then exert their bystander killing effect.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This phenomenon was not related to a greater or lesser potent inhibitory effect on the proliferation of the transfected tumor cells. Recent observations criticizing the conventional gap junction model based solely on size restriction, [34][35][36] are consistent with our hypothesis that gap junction might be differentially permeable to a variety of nucleotides. Purine nucleoside analogues may effectively cross the gap junctions once they have been converted to their monophosphate form (by the viral TK) and then exert their bystander killing effect.…”
Section: Discussionsupporting
confidence: 90%
“…However, Cao and coworkers 34 recently concluded from fluorescent dye transfer experiments with Cx32, Cx26 and Cx45 genetransfected cells that not molecular size but other molecular characteristics, such as charge determine gap junction permeability. Also, experimental data from Veenstra et al 35,36 suggested a new gap junction model based on ionchannel interactions or electrostatic charge effects (as seen in multistate ion channels) rather than the conventional aqueous pore gap junction model. How the cells would discriminate between purine and pyrimidine nucleotides in this model is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…9 When expressed individually in "communication-deficient" cells, each of the cardiac connexins forms channels with distinct unitary conductances, voltage sensitivities, and different capacities to pass anions, cations, or fluorescent dyes of varying sizes and charge densities. 10 These observations suggest that the number, spatial distribution, and connexin composition of gap junction channels are important determinants of the conduction properties of a given cardiac tissue. Regional alterations in connexin expression phenotypes or gap junction distribution induced under a variety of pathophysiological conditions could produce considerable functional heterogeneity within the ventricle.…”
Section: Intercellular Coupling At Gap Junctionsmentioning
confidence: 98%
“…Connexins are an extensive family of proteins comprising several members (Willecke et al, 2002). Different connexins are expressed in different tissues and have different selectivity related to the size and charge of the communicated molecules (Veenstra, 1996). Studies have revealed that channels composed of different connexins have different conductances and permeability to ions and specific fluorescent dyes, and that the rate of permeation is dependent on the connexin composition of the gap-junction channel (Elfgang et al, 1995;Goldberg et al, 1999).…”
Section: Role Of Gjicmentioning
confidence: 99%